A genome-wide association study of pulmonary tuberculosis in Morocco - Grant, A. V.; Sabri, A.; Abid, A.; Abderrahmani Rhorfi, I.; Benkirane, M.; Souhi, H.; Naji Amrani, H.; Alaoui-Tahiri, K.; Gharbaoui, Y.; Lazrak, F.; Sentissi, I.; Manessouri, M.; et al. (Human genetics, 2016)
Although epidemiological evidence suggests a human genetic basis of pulmonary tuberculosis (PTB) susceptibility, the identification of specific genes and alleles influencing PTB risk has proven to be difficult. Previous genome-wide association (GWA) studies have identified only three novel loci with modest effect sizes in sub-Saharan African and Russian populations. We performed a GWA study of 550,352 autosomal SNPs in a family-based discovery Moroccan sample (on the full population and on the subset with PTB diagnosis at <25 years), which identified 143 SNPs with p < 1 × 10 −4 . The replication study in an independent case/control sample identified four SNPs displaying a p < 0.01 implicating the same risk allele. In the combined sample including 556 PTB subjects and 650 controls these four SNPs showed suggestive association (2 × 10 −6 < p < 4  × 10 −5 ): rs358793 and rs17590261 were intergenic, while rs6786408 and rs916943 were located in introns of FOXP1 and AGMO , respectively. Both genes are involved in the function of macrophages, which are the site of latency and reactivation of Mycobacterium tuberculosis. The most significant finding ( p = 2 × 10 −6 ) was obtained for the AGMO SNP in an early (<25 years) age-at-onset subset, confirming the importance of considering age-at-onset to decipher the genetic basis of PTB. Although only suggestive, these findings highlight several avenues for future research in the human genetics of PTB.